2018
DOI: 10.1021/acscatal.8b03102
|View full text |Cite
|
Sign up to set email alerts
|

Online Kinetics Study of Oxidative Coupling of Methane over La2O3 for Methane Activation: What Is Behind the Distinguished Light-off Temperatures?

Abstract: Oxidative coupling of methane (OCM) is a catalytic partial oxidation process that converts methane directly to valuable C2 products (ethane and ethylene). The main difficulties from further investigation of this reaction are due to the nature of its high operating temperature and the severe reaction exothermicity. In this work, an especially designed online characterization setup is applied for this reaction, which achieved both precise bed temperature control and real-time product measurement. High-resolution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 56 publications
7
48
0
Order By: Relevance
“…It is considered as one of the promising ethylene production processes (Galadima and Muraza, 2016;Taifan and Baltrusaitis, 2016). Previous publications (Le Van, 1993;Lacombe et al, 1995;Xu et al, 1995), including our recent in situ studies, indicated that La 2 O 3 is not stable in this reaction (Liu et al, 2018;Li et al, 2019;Guan et al, 2021;Pang et al, 2021;Zhou et al, 2021). In our recent studies, it was strongly suggested that a high temperature (800°C) precleaned sample surface, which is free of carbonates and hydroxyls, is enriched with a specific subsurface peroxide species (Zhou et al, 2021).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…It is considered as one of the promising ethylene production processes (Galadima and Muraza, 2016;Taifan and Baltrusaitis, 2016). Previous publications (Le Van, 1993;Lacombe et al, 1995;Xu et al, 1995), including our recent in situ studies, indicated that La 2 O 3 is not stable in this reaction (Liu et al, 2018;Li et al, 2019;Guan et al, 2021;Pang et al, 2021;Zhou et al, 2021). In our recent studies, it was strongly suggested that a high temperature (800°C) precleaned sample surface, which is free of carbonates and hydroxyls, is enriched with a specific subsurface peroxide species (Zhou et al, 2021).…”
Section: Introductionmentioning
confidence: 74%
“…The SEM result indicates the sample is in the shape of nanorods with 10 nm diameter in average. BET measurement (N 2 ) yields specific surface area of 3.4 m 2 /g (Liu et al, 2018).…”
Section: Sample Preparationmentioning
confidence: 99%
“…The minor impact of temperature on catalyst ranking is encouraging in terms of comparing isothermal experimental data from different sources. Pronounced deviations from ideal isothermal operation 37,59 , which undoubtedly influence the catalytic performance, might not be the most influential factor in the ranking and, hence, OCM catalyst selection. Afterwards, the impact of the methane-to-oxygen ratio at a fixed operating temperature was assessed (Figure 3/D).…”
Section: Impact Of Operating Conditions On the Catalyst Rankingmentioning
confidence: 99%
“…In fact, the consecutive oxidation of the products was found to be much less significant in an oxygen-lean environment (high CH4/O2) thanks to the reduced availability of the oxidant. Mainly, because the limited amount of oxygen in the gas phase is already consumed in the unavoidable and undesired oxidation of CH3 radicals 37 .…”
Section: Mechanistic Insights Into Suitable Catalysts For Adiabatic Omentioning
confidence: 99%
“…Since the pioneering work of Keller and Bhasin in the early 1980s [18], hundreds of catalytic materials composed of 68 elements have been investigated for OCM reaction [19]. Due to the high binding energy of CH3−H bond (435 kJ mol −1 ), oxidative coupling of methane generally proceeds at high temperatures (≥ 700 °C) [20]. Because the high temperature process requires special materials for construction, high energy consumption and great capital input, the minimum criteria of C2 yield for industrial application is 30% [21].…”
Section: Introductionmentioning
confidence: 99%